1997
DOI: 10.1046/j.1537-2995.1997.37797369448.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of biologically active lipids with the development of transfusion‐related acute lung injury: a retrospective study

Abstract: TRALI is the result of two clinical events, the first being a predisposing clinical condition and the second being the transfusion of biologically active lipids in stored blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
446
2
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(466 citation statements)
references
References 20 publications
11
446
2
7
Order By: Relevance
“…The second theory is that neutrophils are activated by biologically active lipids such as lysophosphatidylcholines that are released from cell membranes as stored blood products break down over time. 150,153 In support of this hypothesis, several studies have suggested that blood products that are stored longer may be more likely to produce TRALI in at-risk groups such as trauma 154 and severe sepsis patients. 155 …”
Section: Alcohol Abusementioning
confidence: 96%
“…The second theory is that neutrophils are activated by biologically active lipids such as lysophosphatidylcholines that are released from cell membranes as stored blood products break down over time. 150,153 In support of this hypothesis, several studies have suggested that blood products that are stored longer may be more likely to produce TRALI in at-risk groups such as trauma 154 and severe sepsis patients. 155 …”
Section: Alcohol Abusementioning
confidence: 96%
“…7,15,20 An alternative mechanism involves accumulation of bioactive lipids (lysophosphatidylcholines [lysoPCs]) during storage of cell containing blood products. [21][22][23] Cardiac surgery patients may be at risk for TRALI. During the intrathoracic surgical procedure, the lungs are deflated and nonventilated for several hours, which may cause injury to the lung vasculature (the "first event").…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These complications (Table 1) include syndromes suspected to be associated with the conditioning regimen or HCT-related treatment, such as radiation-induced lung injury, [3][4][5][6] drug toxicity, [7][8][9][10] pulmonary veno-occlusive disease (PVOD), [11][12][13] engraftment syndrome, [14][15][16][17] transfusion-related lung injury (TRA-LI), 18,19 idiopathic pneumonia syndrome, [20][21][22][23][24] and diffuse alveolar hemorrhage, [25][26][27][28] as well as syndromes suspected to be a consequence of alloreactive activity, such as chronic airflow obstruction (AFO), [29][30][31][32][33][34][35] bronchiolitis obliterans syndrome (BOS), 33,[36][37][38] and bronchiolitis obliterans organizing pneumonia. [14][15][16][17]39 Although the predictive value of pretransplant pulmonary function testing (PFT) is somewhat controversial, most HCT institutions perform routine pretransplant lung function assessment as a baseline reference, in anticipation of these potential pulmonary toxicities.…”
mentioning
confidence: 99%